Isolation and Characterization of the Stress-Tolerant Candida tropicalis YHJ1 and Evaluation of Its Xylose Reductase for Xylitol Production From Acid Pre-treatment Wastewater - Kim, Seonghun; Lee, Jinhyuk; Sung, Bong Hyun (Frontiers in Bioengineering and Biotechnology, 2019)
A stress-tolerant yeast was isolated from honey using acid hydrolysate generated from sequential acid-/alkali-pretreatment of empty palm fruit bunch fiber (EPFBF). The isolated yeast was identified molecularly, taxonomically, and morphologically as Candida tropicalis YHJ1, and analyzed for application in xylitol production. The isolated yeast showed stress tolerance toward various chemical reagents and could grow with up to 600 g/L xylose in the culture medium. This yeast also had a broad carbohydrate utilization spectrum, and its xylitol yield was greatest in medium supplemented with xylose as the sole carbon source. In batch fermentation for xylitol production, the yeast could convert xylose prepared from acidic EPFBF pretreatment wastewater into xylitol. Interestingly, C. tropicalis YHJ1 xylose reductase, containing a Ser279 residue, exhibited more effective xylitol conversion compared to orthologous Candida enzymes containing Leu279 or Asn279; this improvement was associated with NADPH binding, as predicted through homologous structure modeling and enzyme kinetic analysis. Taken together, these results show a novel stress-tolerant yeast strain that may be applicable to xylitol production from toxic lignocellulosic byproducts.